Diagnosis of Methyl Malonicaciduria from 2013 to 2018 - Alina Concepción Álvarez; Ivette Camayd Viera; Norma Elena de León Ojeda; Alina García García; Laritza Martínez Rey; Daniel Quintana Hernández (Revista Finlay)
Foundation: methylmalonic aciduria is one of the most frequent organic acidurias and groups together a set of genetic defects, characterized by the excretion of elevated levels of urinemethyl malonic acid. The excretion of this metabolite may or may not be accompanied by elevated homocysteine levels depending on the affected metabolic pathway. Objective: to describe the implementation of a laboratory methodology that combines methylmalonic acid and homocysteine in the differential diagnosis and monitoring of methylmalonic aciduria in the period from 2013 to 2018. Methods: for patients with an increase in methylmalonic acid in the organic acid profile, homocysteine was quantified in plasma and urine. The identification of methylmalonic acid was performed by gas chromatography / mass spectrometry, while the homocysteine quantification by high performance liquid chromatography. Results: chromatographic methods allowed the identification and quantification of methylmalonic acid and homocysteine, respectively. Homocysteine was quantified in seven patients with increased levels of methylmalonic aciduria. Homocysteine levels in four of them were higher than normal values, suggesting aciduria combined with homocystinuria. Three of the patients with combined methylmalonic aciduria under treatment showed a decrease in the levels of both metabolites, corresponding to a satisfactory evolution. Conclusions: simultaneous determination of both markers allowed differential diagnosis and biochemical monitoring of this disease.